Geometric control and nonsmooth analysis : in honor of the 73rd birthday of H. Hermes and of the 71st birthday of R.T. Rockafellar - Ancona, Fabio, 1964-; Hermes, Henry, 1933-; Rockafellar, R. Tyrrell, 1935- (Series on advances in mathematics for applied sciences, 2008)
The aim of this volume is to provide a synthetic account of past research, to give an up-to-date guide to current intertwined developments of control theory and nonsmooth analysis, and also to point to future research directions.